Urgency of BPJS Policy Specifically for Farmers in Improving Farmer Welfare in Indonesia - Rabith Madah Khulaili Harsya; Bunga Mardhotillah; Erlita Khrisinta Dewi; Pande Ayu Naya Kasih Permatananda; Hotnida Nainggolan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is qualitative with a descriptive approach. The data used in this study are secondary data obtained by the researcher from indirect sources such as books, scientific articles, magazines, and so on. The data obtained were analyzed through the stages of data collection, data reduction, data selection, and conclusion drawing. The conclusion in this article show that the implementation of BPJS or health insurance for farmers has a very urgent meaning for the welfare explained in several previous paragraphs, namely related to economic sovereignty, peace, and happiness. With BPJS or health insurance for farmers, it can anticipate unexpected expenses related to farmers' health. Farmers can feel safer and happier, and can focus more on business development, increasing income, and improving product creativity. Thus, the researcher concludes, the implementation of BPJS specifically for farmers has a very close urgency in creating farmer welfare.